Development of an Internet of things system for smart home HVAC monitoring and control - Alves, Aníbal A. (2020)
This paper presents the development and test of an Internet of Things (IoT) system applied to the monitoring and control of an HVAC (Heating, Ventilation and Air Conditioning) system that includes parameters such as temperature, humidity, air quality, human presence and smoke detection. For this purpose, a hybrid wireless network combining Bluetooth Low Energy (BLE) and IEEE 802.11/Wi-Fi was implemented inside a house. An online database for the synchronization of the HVAC data, which was developed using the Amazon Web Services (AWS) cloud platform, allows the user to access the data and control the system parameters through the Internet using an Android mobile app. A smart temperature control system was also developed in the BLE/Wi-Fi gateway to keep the room temperature inside a user-defined range. The functionalities and performance of the proposed system were both validated through experimental tests.